OsGASR9 positively regulates grain size and yield in rice (Oryza sativa). (September 2019) - Li, Xiangbo; Shi, Shuangyue; Tao, Quandan; Tao, Yajun; Miao, Jun; Peng, Xiuron; Li, Chang; Yang, Zefeng; Zhou, Yong; Liang, Guohua
Highlights: OsGASR9 transcripts were detected in various tissues, with the highest level in panicles. Higher mRNA of OsGASR9 accumulated in young than in old panicles and spikelets. OsGASR9 positively regulates grain size and weight, and increases the yield production in the NIP background. OsGASR9 may regulate plant height, grain size and yield through GA pathway and could have an application value in breeding. Abstract: The plant-specific gibberellic acid (GA)-stimulated transcript gene family is critical for plant growth and development. There are 10 family members in rice ( Oryza sativa ), known as OsGASR s. However, few have been functionally characterized. Here, we investigated the function of OsGASR9 in rice. OsGASR9 transcripts were detected in various tissues, with the lowest and highest levels in leaves and panicles, respectively. Greater mRNA levels accumulated in young, compared with in old, panicles and spikelets. OsGASR9 localized to the plasma membrane, cytoplasm and nucleus. Transgenic RNA interference-derived lines in the Zhonghua 11 background exhibited reduced plant height, grain size and yield compared with the wild-type. The two osgasr9 mutants in the Nipponbare background showed similar phenotypes. Conversely, the overexpression of OsGASR9 in the two backgrounds increased plant height and grain size. A significantly increased grain yield per plant was also observed in the overexpression lines having a Nipponbare background. Furthermore, by measuring the GA-induced lengths of the second leaf sheaths and α-amylase activity levels of seeds, we concluded that OsGASR9 is a positive regulator of responses to GA in rice. Thus, OsGASR9 may regulate plant height, grain size and yield through the GA pathway and could have an application value in breeding.